ANALISIS SISTEM ANTRIAN PADA LOKET PEMBAYARAN PT. PLN (PERSERO) AREA BALI SELATAN RAYON KUTA - PRABA MARTHA, NGURAH GDE; SUKARSA, KOMANG GDE; NILA KENCANA, I PUTU EKA (E-Jurnal Matematika; Volume 1, No 1, Tahun 2012DO - 10.24843/MTK.2012.v01.i01.p002, 2012)
The purpose of the analysis of queuing systems is to find out the model and the performance of queuing system was run. The research was conducted at PT. PLN (Persero) South Bali Area Rayon Kuta and the issue raised is about the analysis of queuing systems at the payment counter. Model queue is determined based on the Kendall notation and performance of queuing systems can be determined by calculating the utilization factor. At payment counter, the queuing model used is a model (M/G/4):(GD/?/?). The performance of queuing system at payment counter of PT. PLN (Persero) South Bali Area Rayon Kuta is less effective because each servers was busy on average only between 30% – 50% of working hours so that more time unemployed servers.
Keywords: Queuing System, Payment Counter, Queuing Model